Reciprocal innovation: A new approach to equitable and mutually beneficial global health partnerships - Thomas G. Sors; Rishika Chauhan O'Brien; Michael L. Scanlon; Li Yuan Bermel; Ibrahim Chikowe; Adrian Gardner; Jepchirchir Kiplagat; Marya Lieberman; Sharon M. Moe; Nydia Morales-Soto; Winstone M. Nyandiko; David Plater; et al. (Taylor & Francis Group, 2023)
ABSTRACTGlobal health researchers often discount mutual learning and benefit to address shared health challenges across high and low- and middle-income settings. Drawing from a 30-year partnership called AMPATH that started between Indiana University in the US and Moi University in Kenya, we describe an innovative approach and program for mutual learning and benefit coined 'reciprocal innovation.' Reciprocal innovation harnesses a bidirectional, co-constituted, and iterative exchange of ideas, resources, and innovations to address shared health challenges across diverse global settings. The success of AMPATH in Kenya, particularly in HIV/AIDS and community health, resulted in several innovations being 'brought back' to the US. To promote the bidirectional flow of learning and innovations, the Indiana CTSI reciprocal innovation program hosts annual meetings of multinational researchers and practitioners to identify shared health challenges, supports pilot grants for projects with reciprocal exchange and benefit, and produces educational and training materials for investigators. The transformative power of global health to address systemic health inequities embraces equitable and reciprocal partnerships with mutual benefit across countries and communities of academics, practitioners, and policymakers. Leveraging a long-standing partnership, the Indiana CTSI has built a reciprocal innovation program with promise to redefine global health for shared wellbeing at a global scale.